Seasonal Variations in Estradiol-17J3, Progesterone and Cortisol levels during estrous cycle in Buffaloes - SINGH, J K; LUDRI, R S; PANDITA, SUJATA (The Indian Journal of Animal Reproduction, 2023)
Variations in cyclic concentrations of Estradiol-l 7J3, Progesterone and Cortisol were determined by RIA for_ one cycle each in five normal cycling buffaloes during summer, winter and rainy seasons. Overall mean values of progesterone were maximum in cold, followed by hot humid and warm seasons, with significant (P<O.0S) differences between seasons. However, highest peak values (2.65±0.91 ng/ml) were observed during hot-humid season. Estradiol- l 7J3 concentrations were higher on the day of estrus, with wide individual variations and remained low thereafter for most of the days of the cycle. Irrespective of the season, higher estradiol values were recorded · during the cycle, particularly around day 3, 6, 10 and Day 3, possibly due to endocrinologically active dominant follicles of different waves in some buffaloes. Circulating cortisol concentrations fluctuated widely between animals (P<0.05) and were higher on the day of estrus, as compared to other days of the cycle, but the differences were not significant. No seasonal variations were recorded in cortisol concentrations.